2019
DOI: 10.34133/2019/9253132
|View full text |Cite
|
Sign up to set email alerts
|

Highly Textured N-Type SnSe Polycrystals with Enhanced Thermoelectric Performance

Abstract: Thermoelectric materials, which directly convert heat into electricity based on the Seebeck effects, have long been investigated for use in semiconductor refrigeration or waste heat recovery. Among them, SnSe has attracted significant attention due to its promising performance in both p-type and n-type crystals; in particular, a higher out-of-plane ZT value could be achieved in n-type SnSe due to its 3D charge and 2D phonon transports. In this work, the thermoelectric transport properties of n-type pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…In n-type SnSe, due to its 3D charge and 2D phonon transports, 287,318 a higher out-of-plane ZT value can be achieved. Enhancement of TE properties in n-type polycrystalline SnSe alloys by optimizing carrier concentration and designing textured microstructures using MA and repeated SPS method was reported by Shang et al 318 The lowest κ lattice ∼ 0.36 Wm −1 K −1 was obtained at 783 K perpendicular to texture direction.…”
Section: Sn Chalcogenides As Te Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In n-type SnSe, due to its 3D charge and 2D phonon transports, 287,318 a higher out-of-plane ZT value can be achieved. Enhancement of TE properties in n-type polycrystalline SnSe alloys by optimizing carrier concentration and designing textured microstructures using MA and repeated SPS method was reported by Shang et al 318 The lowest κ lattice ∼ 0.36 Wm −1 K −1 was obtained at 783 K perpendicular to texture direction.…”
Section: Sn Chalcogenides As Te Materialsmentioning
confidence: 99%
“…In n-type SnSe, due to its 3D charge and 2D phonon transports, 287,318 a higher out-of-plane ZT value can be achieved. Enhancement of TE properties in n-type polycrystalline SnSe alloys by optimizing carrier concentration and designing textured microstructures using MA and repeated SPS method was reported by Shang et al 318 The lowest κ lattice ∼ 0.36 Wm −1 K −1 was obtained at 783 K perpendicular to texture direction. Enhancement of PF to 681.3 μW m −1 K −2 was observed in perpendicular and parallel directions to the texture in Sn 1.005 Se 0.94 Br 0.06 at 783 K, this leads to a maximum ZT ∼ 1.5 at 783 K. In a reported work, Ge et al 319 demonstrated how three-step doping turned polycrystalline p-type SnSe into n-type, and then the TE performance was enhanced.…”
Section: Sn Chalcogenides As Te Materialsmentioning
confidence: 99%
“…While the extraordinarily thermoelectric performance of SnSe benefits from its single-crystal crystallization, the thermoelectric performance for the polycrystalline sample is still far from being satisfactory [13,14]. Several approaches have been proposed to enhance the thermoelectric performance of bulk group IV-VI compounds, such as intrinsic vacancy [15], defect dopants [16], substitutional doping [17,18], alloying [19], nanostructuring [20], strain lattice [21], and textural microstructure [22] to modify electronic structure, enhance the carrier concentration, or reduce the thermal conductivity. The group IV-VI compounds possess a puckered two-layered structure, and the two layers are interconnected with weak van der Waals forces, while the atoms in the layer form strong covalent interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some concepts and strategies including band convergence [ 5 , 6 ], band nestification [ 7 ], resonant level [ 8 , 9 ], and energy filtering [ 10 , 11 ] have been successfully adopted to optimize the electrical transport properties. On the other hand, progresses on reducing the lattice thermal conductivity κ L , the sole independent parameter, are also achieved by introducing nanostructuring [ 12 , 13 ], point defect [ 14 16 ], dislocation [ 17 , 18 ], lattice anharmonicity [ 19 , 20 ], as well as liquid-like phonons [ 21 , 22 ] or exploring materials with complex crystal structure [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%